PERGESERAN KOMPETENSI PERADILAN TATA USAHA NEGARA PASCA DIUNDANGKAN UNDANG-UNDANG NOMOR 30 TAHUN 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Iskatrinah, Iskatrinah (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2020)
One of the characteristics of State Administrative Law, among others, states that the field of state administrative law is difficult to codify because its arrangements are scattered in various institutions / institutions / government agencies. However, difficult does not mean it can not be done. The promulgation of Law 30 of 2014 concerning Government Administration proves that there has been a codification of the law governing the practice of government administration, therefore it is expected to be able to reinforce the existence of the State Administrative Court in administrative law enforcement. Through this paper, the author tries to explain the authority of the State Administrative Court after the Government Administration Act. This research uses the Normative Juridical Approach method, by tracing, examining the object of research through its legal principles, through its laws and legal history, which is used to find out the rationale, background of the legislation that is the object of research, namely the Law 30 of 2014 concerning Government Administration. So at the end of this study it can be concluded that the enactment of Law Number 30 of 2004 concerning Government Administration has increasingly complemented and strengthened the role of the State Administrative Court in the order of administrative law in Indonesia, and as a legal political basis for law enforcement in state administration